Molecular Biomarkers to characterize Amanita ponderosa mushrooms - Caldeira, A Teresa (2012)
Amanita ponderosa strains are wild mushroom, edible, with a high exportation potential. This specie grows spontaneously in some microclimates in Iberian Peninsula, due to its Mediterranean characteristics, namely in Alentejo and Andaluzia. Due to the great diversity of wild mushrooms, it is essential be able to differentiate and identify the several edible mushrooms species. RAPD markers have been used as a valuable tool to distinguish different genotypes in edible mushrooms; however, it’s a new approach, for Amanita ponderosa strains. In the present study six Amanita ponderosa strains were compared with others Basidiomycetes (Pleurotus ostreatus, Lactarius deliciosus and Coriolus versicolor) and one Ascomycete strain (Tuber sp.) in order to establish different genetic fingerprintings profiles between strains. Molecular profiles were analyzed by RAPD-PCR using eight micosatelites primers and by MSP-PCR using the M13. Results showed that different patterns were generated for each nine strains tested. RAPD analysis enabled to differentiate at species and strain level, however, the degree of discrimination by means of RAPD-PCR depends highly on the primers used. The MSP-PCR is a fast method to amplified DNA polymorphic sequences, with high reproducibility and similarity for the same specie that allow to characterise the genetic profile of the edible mushrooms Tuber sp., Lactarius deliciosus, Pleurotus ostreatus and Amanita ponderosa. Moreover, constitute a valuable tool to distinguish the different genotypes of Amanita ponderosa strains, allowing to identify at specie level and to differentiate A. ponderosa strains from each origin sites.